Influence of neem oil-coated urea and maxican lilac (Gliricidia sepium) as green-manure on transformation of soil nitrogen in rice (Oriza sativa)wheat (Triticum aestivum) system in Typic Hapluestert - SINGH, MUNESHWAR; TAKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
A study was carried out to evaluate the influence of neem oil-coated urea and green-manure on N-use efficiency andtransformation of organic fractions of soil nitrogen and their residual effect under rice (Oryza sativa L.)-wheat (Triticumaestivum L. emend. Fiori & Paol.) system in Vertisol. Application of neem oil-coated urea and lac-coated urea increased the grain yield of rice respectively by nearly 15 and 16%, with a residual effect of 41 and 48% compared with prilled urea. Incorporation of green-manure through mexican lilac (Gliricidia sepium L.) also increased the grain yield of both the crops. The coating of neem oil on urea increased the N-use efficiency by 13.8%. Application of N through neem oil-coated urea and lac-coated urea and the incorporation of green-manure to rice increased the total hydrolyzable N, amino acid N, amino sugar N, hydrolyzable ammonia N, hydrolyzable unidentified N and non-hydrolyzable N. Their application after wheat reduced the amino acid N, amino sugar N and hydrolyzable ammonia N, but their level was more than under prilled urea and the initial level. Incorporation of mexical lilac increased the hydrolyzable unidentified N after rice as well as wheat. Correlation studies between different fractions of organic N and yield and the uptakeof rice and wheat indicated that total hydrolyzable N, amino sugar N, hydrolyzable ammonia N and amino acid N are the active components of the available pool of nitrogen in the plant.